Diffractive pedagogies: dancing across new materialist imaginaries. Issue 2 (23rd February 2016) - Hickey-Moody, Anna; Palmer, Helen; Sayers, Esther
ABSTRACT: We theorise an interdisciplinary arts practice university course and consider the forms of educational imaginary challenged by our curriculum. We argue for the disruptive and generative potential of what we call diffractive pedagogy as an example of the type of learning that can take place when materiality and entanglement are considered as vital constituents. Through self-expression and interweaving across disciplinary boundaries, the potential to produce, embody and theorise simultaneously can be realised. Student bodies do not exist in isolation from one another, or from the environment. It is indeed impossible to separate the dancer from the dance, the teacher from the student, and the bodies from the environments and objects to which they relate. This being true, our student body reproduced our teaching bodies as abject, as messy and peripheral to their imaginings of university education. Materially, student bodies remade the limits to which their consciousness was imaginatively drawn. Through our embodied work, unconscious change began the processes of affecting students' imaginaries of university education.